Identifying Promising Immunomodulators for Type 1 Diabetes (T1D) and Islet Transplantation - Nida Ajmal; Maislin C. Bogart; Palwasha Khan; Ibiagbani M. Max-Harry; Amber M. Healy; Craig S. Nunemaker (Journal of Diabetes Research)
Type 1 diabetes (T1D) is an autoimmune chronic disorder that damages beta cells in the pancreatic islets of Langerhans and results in hyperglycemia due to the loss of insulin. Exogenous insulin therapy can save lives but does not stop disease progression. Thus, an effective therapy may require beta cell restoration and suppression of the autoimmune response. However, currently, there are no treatment options available that can reverse T1D. Within the National Clinical Trial (NCT) database, a majority of over 3000 trials to treat T1D are devoted to insulin therapy. This review focuses on noninsulin pharmacological therapies, specifically immunomodulators. Many investigational new drugs fall under this category, such as the recently FDA-approved CD3 monoclonal antibody teplizumab to delay the onset of T1D. In total, we identified 39 different immunomodulatory investigational drugs. FDA-approved teplizumab for Stage 2 T1D is discussed along with other immunomodulators that have been tested in Phase 3 clinical trials or higher, including otelixizumab (another anti-CD3 monoclonal antibody), daclizumab (an anti-CD25 monoclonal antibody), ladarixin (CXCR1/2 inhibitor), and antithymocyte globulin (ATG). Immunomodulators also play roles in islet transplantation and cellular therapies like FDA-approved Lantidra. Several immunomodulators involved in Phase 3 clinical studies of islet transplantation are also discussed, including alemtuzumab, basiliximab, etanercept, and reparixin, some already FDA-approved for other uses. These include alemtuzumab, basiliximab, etanercept, and reparixin, some of which have been FDA-approved for other uses. This review provides background, mechanism of action, results of completed trials, and adverse effects as well as details regarding ongoing clinical trials for each of these immunomodulators.